Strategies of Conventional Traders in the Era of Online Shop Growth at Batu Merah Market, Ambon City, Maluku Province - Khadijah, Siti; Pinoa, Wiclif Sepnath; Tetelepta, Edward Gland (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Trade is one of the sectors in our economic system that connects the production sector with consumption. This research aims to understand the survival strategies of conventional traders amid the development of online shops in the Batu Merah Market, Ambon City, Maluku Province. The research type used in this study is descriptive with a qualitative approach, and it is analyzed using SWOT analysis. The research results show that strategies implemented to sustain their businesses have been practiced for a long time, including store layout arrangement, expanding the range of merchandise, and being able to withstand the intensifying competition with modern retailers. The presence of online shops offering convenient shopping experiences tailored to customer demands, allowing people to shop from home, has led to a tendency for the community to move away from traditional stores.